THE ROLE OF NURSES IN THE APPLICATION OF CONTROL DIARY TO PATIENTS WITH BRONCHIAL ASTHMA (Conferencea, 2022)
Severe asthma has major adverse effects on patients’ quality of life, the use of healthcare resources and society as a whole. Asthma exacerbations can be fatal, and many deaths could probably be avoided with appropriate patient support, management and referral. Nurses in primary care play a key role in checking how well patients are managing their condition and refer them when appropriate. In specialist severe asthma services, respiratory nurse specialists assess patients, help define their asthma subtype and administer novel therapies. This article provides an overview of severe asthma management and the role of nurses. Asthma is a chronic inflammatory disease of the lungs with complex aetiology. Patients’ airways become hyper-responsive to certain triggers, including animal fur, tobacco smoke, house dust mites, pollution and pollen. Exposure to a trigger promotes bronchoconstriction and airway inflammation, leading to ongoing infiltration of inflammatory cells (including eosinophils, basophils and mast cells), secretion of pro-inflammatory cytokines (including interleukin [IL]-4, IL-5 and IL-13) and accumulation of inflammatory cells in the airways (Chung, 2015). Ongoing airway inflammation results in a thickening of the airway smooth muscle, which increases bronchoconstriction and gives rise to the characteristic signs and symptoms of asthma. These include excessive mucus formation, breathlessness, wheezing and cough (Chung, 2015; Burns, 2013).